Of undines, painters, Writers and storytellers - Bravo Banderas, Leticia (Ondina - Ondine, 2021)
From the most remote Antiquity to our days, the nymphs of the waters have led legends, histories and stories that speak to us about the fascination that the supernatural beings exercise on the human beings, as well as of the impossibility of the love between some and others. The undines lead a great part of these statements. Also they have been an inspiration for the painters mainly from the Romanticism. Undine, of the young but already consecrated, Benjamin Lacombe brings together in a magisterial way both elements and shows once again the force of the classic motives and of the traditional folklore.Key words: undines, literature, Romanticism, Pre-Raphaelitism, tradition, creation, avant-garde.